Analysis of molecular mechanism of Chinese medicine Jinhong decoction (JHD) in synergistically treating sepsis and COVID-19 based on network pharmacology - Jinghan Fan; Yang Yang; Fan Zhang; Xiaowei Wu; Jiajun Li; Li Liang; Qi Tang; Bo Yan; Jiancheng Zhang; Xuming Pan; Guangjun Jin; Changlong Wei; et al. (PLoS ONE, 2025)
Sepsis and COVID-19 are the two mutually-reinforcing risk factors, whose interaction drastically increases mortality rate. Jinhong decoction (JHD) as a Chinese medicine exhibits clinical efficacy against them, but related action mechanism remains to be explored. To this end, using network pharmacology, this study screened active ingredients of JHD and their targets from TCMSP, HERB, PubChem and SwissTargetPrediction databases as well as the targets for these two diseases from DisGeNET, OMIM, Drugbank, TTD, and GeneCards. By intersecting drug and disease targets, we identified common targets and constructed a drug-ingredient-target network. GO and KEGG enrichment analyses revealed key target-related signaling pathways, and transcriptomics analysis further validated tissue distribution of these targets and their expressions. Our identified six key target genes ( AKT1 , MMP9 , ICAM1 , TLR4 , BCL2 , and HIF1A ) were mainly involved in the regulations of immunometabolism, inflammation, and cell survival in both diseases. Functional enrichment analysis indicated that JHD displayed synergistic efficacy against both diseases by simultaneously modulating HIF-1, TNF, and NF-κB signaling pathways. Tissue distribution analyses of these 6 key target genes revealed that CD33 + myeloid cells, fetal lung cells, and bronchial epithelial cells might play an important role in treating both diseases. Overall, this study demonstrates that JHD treats sepsis and COVID-19 through a multi-ingredient, multi-target, and multi-pathway inter-related mechanism, exhibiting a great application potential.